Effects of leucine supplementation on muscle protein synthesis and degradation pathways in broilers at constant dietary concentrations of isoleucine and valine - Zeitz, Johanna O; Käding, Stella-Christin; Niewalda, Ines R; Machander, Vlastislav; de Paula Dorigam, Juliano Cesar; Eder, Klaus (Archives of animal nutrition, 2019)
The present study investigated the hypothesis that dietary concentrations of leucine (Leu) in excess of the breeder´s recommendations activates protein synthesis and decreases protein degradation in muscle of broilers. Day-old male Ross 308 broilers (n = 450) were phase-fed corn-soybean meal-based diets during starter (d 1-10), grower (d 11-22), and finisher (d 23-34) period. The basal diets fed to the control group (L0) met the broilers' requirements for nutrients and amino acids, and contained Leu, Leu:isoleucine (Ile) and Leu:valine (Val) ratios, close to those recommended by the breeder (Leu:Ile: 100:54, 100:52, 100:51; Leu:Val 100:64, 100:61, 100:58; in starter, grower and finisher diet, resp.). Basal diets were supplemented with Leu to exceed the breeder's recommendations by 35% (group L35) and 60% (group L60). Growth performance during 34 d, and carcass weights, and breast and thigh muscle weights on d 34 were similar among groups. Hepatic and muscle mRNA levels of genes involved in the somatotropic axis [growth hormone receptor, insulin-like growth factor (IGF)-1, IGF binding protein 2, IGF receptor] on d 34 were not influenced by Leu. In the breast muscle, relative mRNA abundances of genes involved in the mammalian target of rapamycin (mTOR) pathway of protein synthesis (mTOR, ribosomal p70 S6 kinase) and the ubiquitin-proteasome pathway of protein degradation (F-box only protein 32, Forkhead box protein O1, Muscle RING-finger protein-1) on d 34 were largely similar among groups. Likewise, relative phosphorylation and thus activation of mTOR and ribosomal protein S6 involved in the mTOR pathway, and of eukaryotic translation initiation factor 2A (eIF2a) involved in the general control nonderepressible 2 (GCN2)/eIF2a pathway of protein synthesis inhibition, were not influenced. These data indicate that dietary Leu concentrations exceeding the broiler´s requirements up to 60% neither influence protein synthesis nor degradation pathways nor muscle growth in growing broilers.
Keywords: messenger RNA; Chickens; Animal Feed; Diet; regulace genové exprese; složení těla; carcass quality; Valine; Animal Nutritional Physiological Phenomena; Muscle Proteins; Leucine; valin; zvířata; hmotnostní přírůstek; protein synthesis; leucine; kosterní svaly; RNA, Messenger; kur domácí; svalové proteiny; Gene Expression Regulation; Male; krmivo pro zvířata; dieta; isoleucin; fyziologie výživy zvířat; potravní doplňky; Muscle, Skeletal; Dietary Supplements; Weight Gain; Body Composition; protein degradation; Isoleucine; Animals; mužské pohlaví; Broiler performance; leucin